Multiple cerebral arteriovenous malformations - Álvarez Caicedo, Diana Carolina; Martínez, Silvina; Martin, Clara; Guevara, María; Montilla, Flor; Rubino, Pablo (Revista Argentina de Neurocirugía, 2025)
Background: arteriovenous malformations (AVMs) are usually single lesions; occasionally, they can present in multiple forms associated with congenital diseases.Objectives: to conduct a literature update on multiple cerebral AVMs and to analyze their prevalence, association with congenital syndromes, and the case series of our institution.Methods: we conducted a cross-sectional, descriptive study based on the medical records of patients with cerebral AVMs between 2011 and 2021 at our institution. We identified those with multiple lesions (2 or more) and their association with congenital syndromes. A literature review was also conducted.Results: according to an analysis of 13 publications including 5882 cases, multiple AVMs represent 1.75% of all patients with AVMs, and are associated with congenital disorders such as Rendu-Osler-Weber syndrome (ROWS) in 50% of cases and Wyburn-Mason syndrome (WMS) in 5.5–23% of patients. In our series, of 157 patients with cerebral AVMs, two presented with multiple lesions (1.27%), and one case was associated with ROWS.Conclusion: multiple cerebral AVMs are rare and require a multidisciplinary team approach due to their high association with congenital syndromes. This entity represented 1.27% of all AVMs treated at our institution and 1.75%, according to analysis in various case series previously reported in the literature. It is most frequently associated with congenital syndromes, such as Rendu-Osler-Weber syndrome, in 50% of cases.
Keywords: Intracranial hemorrhage; Multiple cerebral arteriovenous malformations; Rendu-Osler-Weber syndrome; Wyburn-Mason syndrome